Prevalence of cardiovascular disease and major risk factors in patients with rheumatoid arthritis: a multinational cross-sectional study - Pappas, Dimitrios A; Nyberg, Fredrik; Kremer, Joel M; Lampl, Kathy; Reed, George W; Horne, Laura; Ho, Meilien; Onofrei, Alina; Malaviya, Anand N; Rillo, Oscar L; Radominski, Sebastiao C; Gal, Janos; et al. (Clinical rheumatology, 2018)
To compare the prevalence of cardiovascular disease (CVD) and major CVD risk factors among rheumatoid arthritis (RA) patients enrolled in a large US and multinational registry. We compared CVD and CVD risk factor prevalence from 11 countries enrolled in the CORRONA US and CORRONA International registries; patients from the 10 ex-US participating countries were grouped by region (Eastern Europe, Latin America, and India). Unadjusted summary data were presented for demographics and disease characteristics; comparisons for prevalence of CVD risk factors and CVD were age/gender standardized to the age/gender distribution of the US enrolled patients. Overall, 25,987 patients were included in this analysis. Compared to patients from the ex-US regions, US participants had longer disease duration and lower disease activity, yet were more likely to receive a biologic agent. Additionally, CORRONA US participants had the highest body mass index (BMI). Enrolled patients in India had the lowest BMI, were more rarely smokers, and had a low prevalence of hyperlipidemia, hypertension, and prior CVD compared to the US and other ex-US regions. Participants from Eastern Europe had a higher prevalence of hypertension and hyperlipidemia and highest prevalence of all manifestations of CVD. Differences in the prevalence of both CVD and major CVD risk factors were observed across the four regions investigated. Observed differences may be influenced by variations in both non-modifiable/modifiable characteristics of patient populations, and may contribute to heterogeneity on the observed safety of investigational and approved therapies in studies involving RA patients from different origins.
Keywords: Female; kardiovaskulární nemoci; hypertenze; revmatoidní artritida; Argentina; Brazil; Cross-Sectional Studies; Indie; mužské pohlaví; rizikové faktory; hyperlipidemie; Arthritis, Rheumatoid; prospektivní studie; Humans; Prevalence; Spojené státy americké; východní Evropa; Europe, Eastern; Prospective Studies; Mexico; průřezové studie; Cardiovascular Diseases; India; registrace; lidé; United States; ženské pohlaví; Risk Factors; Mexiko; Hypertension; Hyperlipidemias; Brazílie; prevalence; Registries; Male